2006
DOI: 10.1002/jrs.1446
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the Raman spectra of drug substances upon laser excitation wavelength

Abstract: The laser excitation wavelength is an important parameter in obtaining definitive Raman spectra from pharmaceutical drug substances. This paper investigates the effect of changing wavelength on the Raman spectra of four different drug substances: paracetamol, paroxetine and ranitidine (polymorphic forms I and II). Excitation wavelengths in the range 244 nm to 785 nm have been used. The fluorescence intensities in the Raman spectra were found to be negligible at the two extreme laser wavelengths but tended to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 7 publications
2
15
0
Order By: Relevance
“…244 nm) is also effective in avoiding fluorescence as it is well separated from the Raman signal. [6] It has been demonstrated that conventional dispersive Raman spectroscopy, with far-red excitation, of N-methyl-3, 4-methylenedioxyamphetamine (MDMA) and related compounds can be very rapid and effective. This type of fluorescence can be avoided if the Raman signal is located in a different region (e.g.…”
Section: Bulk Street Drugsmentioning
confidence: 99%
“…244 nm) is also effective in avoiding fluorescence as it is well separated from the Raman signal. [6] It has been demonstrated that conventional dispersive Raman spectroscopy, with far-red excitation, of N-methyl-3, 4-methylenedioxyamphetamine (MDMA) and related compounds can be very rapid and effective. This type of fluorescence can be avoided if the Raman signal is located in a different region (e.g.…”
Section: Bulk Street Drugsmentioning
confidence: 99%
“…This shift provides information about vibrational, rotational and other low frequency transitions in molecules. Raman spectroscopy can be used to study solid, liquid and gaseous samples [2][3][4][5]. A Raman system typically consists of four major components: Excitation source (Laser), Sample illumination system and light collection optics, Wavelength selector (Filter or Spectrophotometer) and Detector (Photodiode array, CCD or PMT).…”
Section: Raman Spectroscopy and Comsol Multiphysics Overviewmentioning
confidence: 99%
“…The final drug concentration was about 10 −6 mol l −1 . A detailed assignment of all vibrational modes suggested the preponderance of the polymorphic form I of paracetamol [23,24]. It is well known that there are two major possibilities of molecular adsorption on the metal surface, namely, physisorption and chemisorption.…”
Section: Sers Of Antipyretics and Analgesicsmentioning
confidence: 99%